OC-088 Risk of oesophageal neoplasia in barrett's oesophagus with indefinite for dysplasia or low grade dysplasia at index biopsy: a 10-year cohort study. (22nd June 2015) - Chan, WY; Pournaras, DJ; Sreedharan, L; Brown, SL; Igali, L; Kumar, B; Cheong, E
Abstract : Introduction: Barrett's oesophagus (BO) is the only recognised precursor for oesophageal adenocarcinoma (OAC). Accurate prediction of progression to high grade dysplasia (HGD) or OAC is important. The literature reports progression rates for indefinite for dysplasia (IND) at 1.2% per patient-year and low grade dysplasia (LGD) at 9% per patient-year. Our study aims to determine incidence of HGD or OAC in patients with confirmed histopathological diagnosis of IND or LGD at index biopsy. Method: Retrospective review of all patients diagnosed with IND or LGD over a 10-year period from January 2003 to September 2014. Two specialist pathologists in Barrett's oesophagus and neoplasia reviewed all histology. Primary end point was progression to HGD or OAC. Patient demographics and grade of endoscopist were recorded. Patients with HGD or OAC at index biopsy were excluded. Results: 85 patients (78.8% male, 100% White British) had LGD; 138 (65.9% males, 100% White British) patients had IND. 47% (n = 40) patients with LGD and 10.1% (n = 14) patients with IND progressed to HGD or OAC in the 10-year period. Median age at progression was 71 years (IQR 61.5 to 75.3) and 68 years (IQR 60.25 to 73.5) for LGD and IND, respectively. Median time of progression from first diagnosis to HGD or OAC was 16 months for both IND and LGD. Median BO length was 7 cm (IQR 5 to 9.75) in LGD and 6 cm (IQR 4.25 to 6.75) in IND. 35% (n = 14) patients with LGD who progressed had an expert upper GI endoscopist performing the endoscopy; in these 14 patients, median time for progression was 5.5 months (IQR 3.25 to 12.75). 67.5% (n = 27) patients with LGD were diagnosed with HGD or OAC 12 months after their last biopsy; the median time to biopsy in the LGD group was 5 months (IQR 1.5 to 6). But 16.8% (n = 15) patients were diagnosed with HGD/OAC at the first follow-up biopsy; the median time to this diagnosis was 5 months (IQR 2.5 to 6). Excluding 5 IND patients who developed OAC within 12 months, median time to progression for IND was 46 months (IQR 18 to 66); 7 patients with IND progressed to HGD, 5 patients progressed to intramucosal adenocarcinoma, and 2 died of inoperable adenocarcinoma. Conclusion: The majority of LGD who progressed occurred in less than 12 months, and median time to diagnosis was 5 months. An expert upper GI endoscopist follow up is warranted for earlier diagnosis and treatment in IND and LGD. Current BSG Guidelines suggest a follow-up surveillance endoscopy should be done at 6 months for confirmed LGD prior to radio-frequency ablation. Our findings suggest these patients should be followed up earlier. LGD should be recognised as a marker of more advanced neoplasia. Disclosure of interest: None Declared.